Використання мікроскопічного методу для знаходження розподілу об’єму частинок харчових порошків за розмірами - Воронцова, Жанна Вадимівна; Павлюк, Ігор Миколайович (Eastern-European Journal of Enterprise Technologies, 2011)
The methods dispersion analysis as applied to food powders. Listed distribution function of the volume of the particle size that allows to made more objective analysis of food powders